Analisis Finansial Usaha Pembenihan Ikan Nila (Oreochromis Niloticus) di Balai Benih Ikan Pendem Jawa Timur - Ali Fahmi Syahputra; indrajit wicaksana (Program Studi Agribisnis, Fakultas Pertanian, Universitas Singaperbangsa Karawang, 2022)
Tilapia is a fish that very easy to cultivate, resistant to disease, suitable for the tropical climate, and has a fairly high economic value. Tilapia is a freshwater fish that widely consumed, especially in developing countries. This study aims to determine the financial aspect, like the operational feasibility of a tilapia hatchery. Data collection was carried out at the Balai Benih Ikan Pendem and the Batu City Agriculture Service. The research method with quantitative analysis includes the amount of capital, total cost, total revenue, income, break even point (BEP), profit, business profitability and revenue cost ratio (R/C ratio). The results of the analysis show that the total cost is Rp. 1,646,500, the total revenue is Rp. 6,000,000, income Rp. 4,353,500, BEP Rp. 903.395.78, profit Rp. 4,353,500, business profitability 264.40% and R/C ratio 3.64 means that this tilapia hatchery business is profitable and feasible.. Keyword: Break Even Point, Income, Profit, R/C Ratio